Aplicação da realidade virtual e aumentada para simulação de projeto na construção civil - Feitosa, Ludimila Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
Virtual Reality and Augmented Reality has been a highlight in the current technology market, the first is the immersion of the user in a virtual environment created by the computer, while the second refers to the ability to put virtual objects in the real environment. The possibility of generating sensations, of visualizing something not yet existent, of providing process optimization, among other aspects, guarantees a greater diversity of applications for these tools. From this scenario, the work had its development in the verification of the feasibility of the application of Virtual and Augmented Reality in the presentation of architectural projects, being able to describe how the technology can assist in the work of Architecture, Engineering and Construction - AEC professionals. To carry out this study and success of the objective, we adopted the quati-qualitative methodology, checking data from bibliographies and scientific productions in the area, as well as demonstrating an application with these techniques and conducting questionnaires with UFERSA students. In this way, it was verified that this application provides a better visualization of the property and understanding of the enterprise, giving the user a greater immersion in the project.
Monografia
Keywords: Realidade Virtual; Realidade Aumentada; Imersão; Projetos; Engenharia; Virtual Reality; Augmented Reality; Immersion; Projects; Engineering; ENGENHARIAS::ENGENHARIA CIVIL